Effect of Reaction Time on Highly Ordered TiO2 Nanotube Arrays Based Dye-Sensitized Solar Cells - Wang, Shanghua; Zhang, Jingbo; Lin, Yuan (Asian Journal of Chemistry, 2012)
Highly ordered TiO2 nanotube arrays (TNAs) were fabricated by anodizing titanium foils in F-containing electrolyte for different time. The crystalline and morphology of the prepared TiO2 nanotube arrays were studied by X-ray diffraction patterns and scanning electron microscope. The influences of reaction time on the prepared TiO2 nanotube arrays were carefully examined. The results showed that the surface area of TiO2 nanotube arrays increased with reaction time, meanwhile resistance on photoanode/electrolyte interface decreased with reaction time. Too long reaction time will not increase the surface area of TiO2 nanotube arrays. When the prepared TiO2 nanotube arrays were used on dye-sensitized solar cells (DSSCs), a light to electricity conversion efficiency (h) of 5.95 % was obtained when illuminated on back side which is a high efficiency considering without further treatment of TiO2 nanotube arrays.